2017
DOI: 10.3390/ijms18050987
|View full text |Cite
|
Sign up to set email alerts
|

AF1q Mediates Tumor Progression in Colorectal Cancer by Regulating AKT Signaling

Abstract: The up-regulation of ALL1-fused gene from chromosome 1q (AF1q) is commonly seen in aggressive hematologic malignancies as well as in several solid tumor tissues. However, its expression and intrinsic function in human colorectal cancer (CRC) remains largely undefined. To explore the role of AF1q in human CRC progression, AF1q expression was analyzed in human CRC tissue samples and CRC cell lines. Clinical specimens revealed that AF1q was up-regulated in human CRC tissues, and that this up-regulation was associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…AF1q expression is reportedly associated with metastatic spread in colorectal, lung, and breast cancer [5,12,36,37]. Since HER-2 is commonly expressed in EC, lung, and breast cancer [38,39,40,41], HER-2 might be another signaling pathway AF1q interacts with.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AF1q expression is reportedly associated with metastatic spread in colorectal, lung, and breast cancer [5,12,36,37]. Since HER-2 is commonly expressed in EC, lung, and breast cancer [38,39,40,41], HER-2 might be another signaling pathway AF1q interacts with.…”
Section: Discussionmentioning
confidence: 99%
“…AF1Q was originally identified as an MLL fusion partner in acute myeloid leukemia patients with a t(1; 11)(q21; q23) translocation ( MLLT11 ); here, multiple chromosomal translocations of the AF1q locus have been described [1]. Enhanced AF1q expression is associated with poor clinical outcome in hematologic and several solid malignancies, such as breast, thyroid as well as testicular cancer and neuroblastoma [2,3,4,5,6,7,8,9]. Further on, AF1q plays a role in cell differentiation and maintenance during neuronal development [10], and is involved in stem cell differentiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interesting candidates include MLLT11 and TRIM13, whose CNAs or differential methylation status have not been reported in OSCC . MLLT11 (1q21.3) is an oncogene dysregulated in some acute myeloid leukemia patients with t(1;11)(q21;q23) translocation and also facilitates the progression of solid tumors [ 69 , 70 ]. Recurrent gains of the 1q21.3 region and upregulation of MLLT11 were reported in the Wilms tumor [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 48 Jingwei Hu et al showed that MLLT11 could regulate the progression of colorectal cancer through AKT. 15 On the other hand, as a component of the TLR4 signaling complex, TRIL plays a vital role in the inflammatory response. 17 , 49 To date, data on the roles of TRIL in tumor development and the specific molecular mechanisms of MLLT11 in regulating AKT remain scant.…”
Section: Discussionmentioning
confidence: 99%